The Effect of Social Capital Dimensions on Entrepreneurial Performances of MSME’s - Razak, Almas Jabeen Abdul; Srinivasulu, Dr. Yarlagadda (The journal of contemporary issues in business and government, 2022)
Since the early 2000s, the phrase "social capital" has been widely explored. The origin of social capital can be can be traced back to 1867 and 1900, when Karl Marx and John Dewey adapted it to fit into a societal context. Intoday’s world, there is an increased appreciation for the importance of social capital and entrepreneurship.The commercial diversification that India possesses, in particular, makes it accountable to utilize social capital. As a result, this research focuses on how social capital influences MSME entrepreneurial performance, taking into account several dimensions of social capital as well as MSME performance. Data was obtained from 390 MSME's in South India using structured questionnaires and analyzed using SPSS and the Structural Equation Modelling (Amos) approach, and it was discovered that social capital dimensions and entrepreneurial performance have a strong association.